Understanding Learning: Insights into Methodology and Conceptualization by Jean Piaget - Muwahidah Nur Hasanah; Ndaru Putri; Syamsudin Syamsudin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
Learning is an activity involving both physical and psychological aspects and is the key element in education. In the current era of globalization, learning is often equated with schooling, although schools are just one of the learning environments for students. The success in achieving educational goals is greatly influenced by the learning process experienced by students as learners. Jean Piaget is an influential theorist in the field of cognitive development of learners. Departing from the aforementioned issues, the researcher aims to uncover the concept of learning and its methods according to Jean Piaget. The research approach used in this study is literature research, whereby in data collection, the researcher utilizes both primary and secondary data. Primary data consists of literature from Jean Piaget's books, while secondary data is obtained from supporting sources. These data are obtained through the documentation method. In the analysis, the researcher employs the content analytical method. From this simple study, the researcher can conclude that: The concept of learning according to Jean Piaget is divided into two understandings, namely figurative learning and operative learning. The objects of learning according to Jean Piaget are thinking, sciences, and arts. The goal of learning according to Jean Piaget is to develop intellectuality and logic, and to develop and plan actions that initially seem excessive into mental operations. Learning methods according to Jean Piaget include top-down processing, cooperative learning, and generative learning. Learning sources according to Jean Piaget are physics, logical mathematics, and social sciences. The scope of learning according to Jean Piaget encompasses parents, environment, and experiences.